Methylglyoxal induces chromosomal instability and mitotic dysfunction in lymphocytes. (23rd July 2021) - Donnellan, Leigh; Simpson, Bradley; Dhillon, Varinderpal S; Costabile, Maurizio; Fenech, Michael; Deo, Permal
Abstract: Type 2 diabetes is associated with elevated levels of DNA damage, in particular micronuclei (MNi) which are formed by acentric chromosome fragments caused by double-stranded DNA breaks (DSBs), or whole chromosomes which fail to segregate during mitosis. We investigated if methylglyoxal (MGO), a reactive dicarbonyl known to be elevated in type 2 diabetes is capable of increasing chromosomal instability and DNA damage as measured by the cytokinesis block micronucleus cytome (CBMNcyt) assay in B-lymphoblastoid WIL2-NS cells and primary peripheral blood lymphocytes (PBL). We also investigated the level of various dicarbonyl stress biomarkers, including extracellular and intracellular MGO, protein and MGO modifications of DNA. WIL2-NS cells exposed to either MGO or a glyoxalase 1 inhibitor showed increases in MNi and nuclear buds, which were associated with an increase in intracellular MGO. DNA damage in the form of MNi and nucleoplasmic bridges were observed in primary PBL exposed to 10 µM MGO, suggesting low concentrations of MGO may be genotoxic. Furthermore, we showed, using fluorescent in situ hybridisation, that the majority of MNi caused by MGO in WIL2-NS cells were caused by whole chromosome loss events, rather than DSBs. Our data suggest that MGO, a reactive metabolite elevated in type 2 diabetes and other pathologies, can affect genomic integrity by impairing chromosome segregation during mitosis.